2016
DOI: 10.1002/jsfa.7902
|View full text |Cite
|
Sign up to set email alerts
|

Feed and fuel: the dual‐purpose advantage of an industrial sweetpotato

Abstract: The CX-1 industrial sweetpotato is an ideal dual-purpose crop for tropical/subtropical climates that can be utilized as a non-grain-based feedstock for bioethanol production while contributing a valuable, high-yielding nutritional supplement for animal feed. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…Beauregard) have the ability to out-produce other sources of crop plant bioethanol (e.g., corn, potatoes, sugar cane, and sugar beets) in both Maryland and Alabama. Roots of the industrial sweetpotato cultivar CX-1, examined in the current study, have been shown to have a higher bioethanol production potential than the table cultivars Hernandez (27.6%) or Beauregard (71.1%; Mussoline and Wilkie, 2017). Given that we observed a large (40.9%) increase in total storage root dry weight production under elevated CO2, it is expected that ethanol yield would have a corresponding increase since 90% of the dry matter in the CX-1 cultivar is carbohydrate (Ryan-Bohac, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beauregard) have the ability to out-produce other sources of crop plant bioethanol (e.g., corn, potatoes, sugar cane, and sugar beets) in both Maryland and Alabama. Roots of the industrial sweetpotato cultivar CX-1, examined in the current study, have been shown to have a higher bioethanol production potential than the table cultivars Hernandez (27.6%) or Beauregard (71.1%; Mussoline and Wilkie, 2017). Given that we observed a large (40.9%) increase in total storage root dry weight production under elevated CO2, it is expected that ethanol yield would have a corresponding increase since 90% of the dry matter in the CX-1 cultivar is carbohydrate (Ryan-Bohac, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, although carbohydrate analysis was not conducted in our study, it can be expected that as the concentration of atmospheric CO2 continues to rise, the CX-1 sweetpotato cultivar will produce more net dry matter carbohydrate yield per hectare which will increase the quantity of bioethanol produced per hectare. The effects of elevated CO2 on ethanol production and use of vines as a nutritional animal feed (Mussoline and Wilkie, 2017) from industrial sweetpotato cultivars, such as CX-1, deserves further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, Ipomoea batatas is considered as a major staple crop especially in developing countries [23]. It is an excellent source of energy with various valuable by-products [24], such as carbohydrates, βcarotene, dietary fibre, minerals and other nutrients, the quantities dependent on the variety [25].…”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato (Ipomoea batatas L.) (Convolvulaceae) is the fourth most consumed vegetable in Brazil, and the sixth most popular and abundant vegetable in the world (MUSSOLINE;WILKIE, 2016). This plant has relatively low production cost, requires minimal investments in technology, and provides a high financial return.…”
Section: Introductionmentioning
confidence: 99%